'Raising the Stakes for Landscape' in the Climate Crisis. (4th January 2022) - Sanjuán, Clara Olóriz
Abstract: It can be argued that landscape gardening and painting have, for centuries, been complicit in the displacement of Indigenous communities, deforestation and creating a changing relationship between humanity and nature that has contributed to the current climate crisis. Clara Olóriz Sanjuán, a co‐director of the Architectural Association (AA) Ground Lab in London, shows us how landscape practices can be reimagined to address these historical injustices.